Controle judicial de políticas públicas: a legitimidade do poder judiciário interferir nas escolhas administrativas para garantir a concretização do mínimo existencial - Lopes Neto, Christiano Dias (2014)
This work deals with public policies judicial review. It is a complex issue, once the case-by-case analyses by the Judiciary cannot rest only just over legal arguments, observing, mainly, the entire factual context that covers such cases and policies. Two of the most controversial questions on this kind of judicial review are whether the Judiciary has legitimacy for it and how it must occur; and a preliminary answer for both is that the Judiciary branch has a limited legitimacy for reviewing public policies. Eight chapters try to confirm this answer. The first shows that the judicial reviewing process does not violate the separation of powers. The second presents the current role played by Public Administration in such scenario, and brings the concept of public policy adopted in this work. Then, third and fourth chapters outline the public policies cycle, one for the planning (third) and other for the execution (fourth) of such policies. The fifth reinforces the previous conclusions indicating that comprehending the cycle guides on how to control public policies. Thus, sixth and seventh chapters bring the restrictions for the public policies judicial review considering the issues on planning (sixth) and on executing (seventh) public policies. Finally, the eighth points out that the Judiciary is non-guiding itself by those restrictions when it reviews public policies. The conclusion, and final answer is that the Judiciary must evaluate how the State must accomplishes its duty of giving effectiveness to constitutional rights, and not only how it must be. For such analyses are employed the hypothetical-deductive method and the dialectical Aristotelian methodology.